2009
DOI: 10.3852/08-169
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of arbuscular mycorrhizal fungi amplified from grapevine roots (Vitis viniferaL.) in Oregon vineyards is seasonally stable and influenced by soil and vine age

Abstract: The diversity of arbuscular mycorrhizal fungi (AMF) in 10 Oregon vineyards was assessed by examining spores in soil and amplifying mycorrhizal DNA from roots. Seventeen spore morphotypes were found in soil, including seven species in the Acaulosporaceae. Eighteen phylotypes were amplified from grape roots with AM1 and NS31 primers, and clones were dominated by Glomus spp. (> 99%). A few clones (< 1%) representing a single phylotype within Gigasporaceae, and a single clone within Archaeosporaceae were amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
61
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 38 publications
11
61
1
3
Order By: Relevance
“…There is no doubt that soil type has a role in the AMF distribution (10,34,35,40,(77)(78)(79)(80), and our work also demonstrated that soil type is a major factor driving AMF assemblages, after elimination of the host factor and other environmental variables not related to soil characteristics. Although individual soil characteristics have been reported to play important roles in AMF community structure and composition (7,11,13,40,42,78,(81)(82)(83), very limited data sets regarding soil characteristics were used in these studies, and the relative incidences of each soil property determined after complete soil characterization have not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that soil type has a role in the AMF distribution (10,34,35,40,(77)(78)(79)(80), and our work also demonstrated that soil type is a major factor driving AMF assemblages, after elimination of the host factor and other environmental variables not related to soil characteristics. Although individual soil characteristics have been reported to play important roles in AMF community structure and composition (7,11,13,40,42,78,(81)(82)(83), very limited data sets regarding soil characteristics were used in these studies, and the relative incidences of each soil property determined after complete soil characterization have not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Both dominant phylotypes are present in the two mofettes, which are separated by 40 m. The evolutionary history of the two dominant taxa cannot be inferred from these data, but it is highly unlikely that the same lineages have evolved independently, so dispersal between the mofettes is the likely explanation. Data from other, more-distant mofette areas will be required to determine the extent of dispersal limitation, if any, although the presence of similar phylotypes in samples from the United States (35) suggests the possibility of long-range dispersal. The fact that the two dominant phylotypes are sister taxa also supports adaptation and local dispersal as an explanation for the pattern observed at this locality.…”
Section: Discussionmentioning
confidence: 99%
“…3). Indeed, in the vineyard, AMF communities are highly influenced by the soil characteristics but also to a smaller extent by the host plant development stage (Schreiner and Mihara 2009;Balestrini et al 2010). Moreover, although AMF from grape roots mainly belong to the Glomerales group, members of the Diversisporales are mainly found in sandy vineyard soils (Balestrini et al 2010).…”
Section: Potential Importance Of Mycorrhizal Diversitymentioning
confidence: 99%
“…Schreiner and Mihara (2009) mainly detected sequences of phylotypes assigned to the Glomeraceae family in a set of ten vineyards in Oregon (USA). Among them was only one known species, nowadays classified as Rhizophagus irregularis, as well as very few Claroideoglomeraceae and Gigasporaceae sequences.…”
Section: Potential Importance Of Mycorrhizal Diversitymentioning
confidence: 99%